2015
DOI: 10.1021/acs.chemmater.5b00945
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Growth of Iron Pyrite FeS2 Nanocrystals via Oriented Attachment

Abstract: Pyrite (FeS2) material is attractive for applications in solar cells, lithium batteries, and hydrogen production because of its abundant, nontoxic features as well as the extraordinary electrical and optical properties. Pyrite (FeS2) nanocrystals (NCs) were synthesized via hot injection method, and the crystalline structure and morphologic evolution of pyrite NCs were investigated. We found that pyrite (FeS2) NCs were generated from a mackinawite FeS0.94 nanosheets template. The initial anisotropic growth of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Pyrite iron disulfide (NiS 2 ) acquires unique morphological structures including nanocrystals, nanowires, nanosheets, nanocubes, and exhibits interesting electrical, photovoltaic, and catalytic properties. [211][212][213][214][215][216][217][218][219][220] An interesting comparative study was done by Shukla et al 221 In an interesting study, FeS 2 nanorod arrays were fabricated on a FTO substrate after sulfurizing FeO(OH) nanorods, and used as a CE for DSSCs. 222 The FeS 2 nanorods exhibited better electrocatalytic activity than FeS 2 films and Pt-based CEs due to more active sites, which resulted in high J SC value of the DSSCs.…”
Section: Fes 2 Based Counter Electrodesmentioning
confidence: 99%
“…Pyrite iron disulfide (NiS 2 ) acquires unique morphological structures including nanocrystals, nanowires, nanosheets, nanocubes, and exhibits interesting electrical, photovoltaic, and catalytic properties. [211][212][213][214][215][216][217][218][219][220] An interesting comparative study was done by Shukla et al 221 In an interesting study, FeS 2 nanorod arrays were fabricated on a FTO substrate after sulfurizing FeO(OH) nanorods, and used as a CE for DSSCs. 222 The FeS 2 nanorods exhibited better electrocatalytic activity than FeS 2 films and Pt-based CEs due to more active sites, which resulted in high J SC value of the DSSCs.…”
Section: Fes 2 Based Counter Electrodesmentioning
confidence: 99%
“…The higher sulfur concentration favours higher FeS 2 formation rate that is the rate‐determining step . A very recent investigation of growth mechanism of FeS 2 NCs by Zhu et al . revealed that OLA in replacement with ODA as a solvent leads to the growth of anisotropic pyrite NCs with more branches, chromosome‐like shapes along the ‹210› direction.…”
Section: Nanocrystalline Pyritementioning
confidence: 99%
“…However, it could not provide further information on how the iron pyrite nanocubes or nanospheres form. Hence, Oriented Attachment (OA), which appears to be a suitable mechanism during the development of nanoscale materials, was introduced in iron pyrite crystalline growth by Gong et al 73 and Zhu et al 85 They utilized the OA mechanism (Fig. 5i) to interpret the iron pyrite cubes and spheres 73 and the anisotropic growth of iron pyrite, 85 respectively.…”
Section: -69mentioning
confidence: 99%